Digitalisasi Dakwah Islam Pondok Pesantren Salaf: Analisis Teori Framing Akun Instagram @limofficial_lirboyo - Hanif, Naufal Aulia; Adaway, Muhammad Amiril; Bagus, Muhammad (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2024)
The purpose of this study is to find out a glimpse of the history of the @limofficial_lirboyo Instagram account, the interpretation of pesantren da'wah in the Disruption Era, and the urgency of the da'wah strategy of the @limofficial_lirboyo account. This qualitative research adapts virtual ethnography and Robert N. Entman's framing theory. The results of this study show that the utilization of the Instagram social media platform by Lirboyo santri is very effective in disseminating Islamic da'wah content as an answer to various problems that arise in society with authoritative knowledge. In addition, the communicative presence of Islamic preaching of Lirboyo santri has a great opportunity to raise the awareness of all Nusantara santri to actively engage in preaching through social media, especially with the intention of grounding the values of moderate Islamic scientific treasures in the process of preaching.